Clinical efficacy and safety of first‐line nilotinib or imatinib therapy in patients with chronic myeloid leukemia—Nationwide real life data - Petra Belohlavkova; Daniela Zackova; Hana Klamova; Edgar Faber; Michal Karas; Lukas Stejskal; Eduard Cmunt; Olga Cerna; Ivana Jeziskova; Katerina Machova Polakova; Pavel Zak; Tereza Jurkova; et al. (Cancer Medicine, 2024)
Abstract Background To evaluate the outcomes of first‐line imatinib versus nilotinib treatment for chronic myeloid leukemia in the chronic phase (CML‐CP) in real‐world clinical practice. Methods A propensity score analysis was performed to eliminate imbalances between the treatment groups. In the analysis, 163 patients in the nilotinib group and 163 patients in the matched imatinib group were retrospectively evaluated. Results Nilotinib‐treated patients achieved complete cytogenetic response (CCyR) and major molecular response more rapidly than imatinib‐treated patients. However, there was no significant difference in 5‐year overall survival (OS) or progression‐free survival (PFS) between the two groups (OS: 94.3% vs. 90.5%, p = 0.602; PFS: 92.9% vs. 88.0%, p = 0.614). Nilotinib‐treated patients had a higher failure‐free survival (FFS) and event‐free survival (EFS) than imatinib‐treated patients (FFS: 71.7% vs. 54.3%, p = 0.040; EFS: 71.7% vs. 53.5%, p = 0.025). Conclusions This retrospective analysis from clinical practice did not confirm any benefit of frontline nilotinib treatment for OS and PFS; however, it did demonstrate higher FFS and EFS in the nilotinib cohort.